Soil biology characteristics of oil palm land endemic to Ganoderma after four years conversion to sugarcane. Issue 1 (March 2020) - Eris, D D; Widiastuti, H; Taniwiryono, D
Abstract: Basal stem rot disease is the primary disease in oil palm production. One of the control methods to keep the disease severity low is through crop rotation by planting non-host crops for a certain period to reduce the pathogen population. This study aimed to evaluate the biological and molecular characteristics of Ganoderma endemic land after converted to sugarcane for four years. Results showed that the total abundance of bacteria in the land ranged from 3.5 × 102–6.1 × 108 CFU/g, whereas phosphates solubilizing bacteria, was in the range of 101–1.0 × 106 CFU/g and N fixing bacteria was 101–2.4 × 104 CFU/g. The genus dominated mycorrhizal fungi from Glomus and Acaulospora with spore population of 1 to 135 spores per 25 g of soil. Another soil biota analyzed was Trichoderma sp. that had population range between 102 to 105 CFU/g. Based on PCR analyses using specific primers Gan2 and Gan3, Ganoderma fungi were still detected in selected soil samples and the remaining roots in the field. Nevertheless, the productivity of sugarcane up to 4 ratoons remained high, i.e. more than 90 t/ha.